2021
DOI: 10.1177/00315125211021239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transcranial Direct Current Stimulation on Professional Female Soccer Players’ Recovery Following Official Matches

Abstract: This study investigated the effect of transcranial direct current stimulation (tDCS) combined with a recovery training session on the well-being and self-perceived recovery of professional female soccer players after official matches. Data from 13 world-class players were analyzed after participating in four official soccer matches of the first division of the Brazilian Women’s Soccer Championship (7-, 10-, and 13-day intervals). We applied anodal tDCS (a-tDCS) over the left dorsolateral prefrontal cortex with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Besides unspecific health- and fitness-related aspects, such as strength, speed, agility, reaction time, balance and coordination, also the athlete's technique and competence level in specific motor skills play an important role 3 . Improving exercise performance is aimed at both, individuals seeking health and fitness (i.e., non-athletes), and those who wish to improve athletic performance (i.e., athletes) 4 . Learning motor skills plays an important role in improving sports performance, which is generally defined as a set of processes aimed at learning and refining new skills by practice 5 , and associated with functional and structural changes in a distributed brain network for example the primary motor area 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides unspecific health- and fitness-related aspects, such as strength, speed, agility, reaction time, balance and coordination, also the athlete's technique and competence level in specific motor skills play an important role 3 . Improving exercise performance is aimed at both, individuals seeking health and fitness (i.e., non-athletes), and those who wish to improve athletic performance (i.e., athletes) 4 . Learning motor skills plays an important role in improving sports performance, which is generally defined as a set of processes aimed at learning and refining new skills by practice 5 , and associated with functional and structural changes in a distributed brain network for example the primary motor area 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The tDCS montages and protocol used in the present study were similar to the study by Etemadi et al [ 30 ]. In M1 and DLPFC conditions, the electric current was gradually ramped up for 30 s, maintained at 2 mA for 20 min, and then progressively ramped down for 30 s. For the sham condition, the DLPFC montage was used but the 2-mA current was maintained active only for 30 s and then was ramped down for 30 s. This sham tDCS procedure has been shown to effectively blind participants [ 30 , 37 39 ]. Moreover, to avoid creating expectations effects [ 40 , 41 ], participants were not informed that there would be a sham stimulation condition [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…In M1 and DLPFC conditions, the current was gradually ramped up for 30 s, maintained at 2 mA for 20 min, and then progressively ramped down for 30 s. In the sham condition, the montage was the same as the DLPFC condition, and the same 30 s ramping up and down was used, but the 2-mA current was only maintained for 30 s. This sham protocol has been used in previous studies and has been shown to induce similar sensations as the active tDCS protocol [ 21 , 64 , 65 ]. Moreover, to make sure that the participants were effectively blinded to the stimulation conditions, they were not informed that there is a sham (inactive) stimulation condition.…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 99%